of 24

• date post

28-Jul-2015
• Category

## Documents

• view

1.428

1

Embed Size (px)

### Transcript of τα πάντα για εξισώσεις

: x+=0 (1) x, - (1). . . 0 (1) , : x = - = 0 0 (1) () = 0 = (1) ( ) o -, . .1. : x - 1 2x - 1 5x - 1+ =2 3 6 x = 2x - 1 2x - 1 5x - 1 x - 1 2x - 1 5x - 1+ = 6 + 6 = 6 3 (x - 1) + 2 (2x - 1) = 5x - 12 3 6 2 3 62x 43x - 3 + 4x - 2 = 5x - 1 3x + 4x - 5x = -1 + 3 + 2 2x = 4 =2 22. 2 : (x - 1) = 4x( - 1) - 3 + 2 = =2( - 2) x = ( - 1)( - 2) - 1x = - 22 2 2 2 22 222 (x - 1) = 4x( - 1) - 3 + 2 x - = 4x - 4x - 3 + 2 x - 4x + 4x = - 3 + 2( - 4 + 4)x = - 3 + 2 () ( - 2) 0, 2, () :( - 1)( - 2) x =( - 2) 2 ( - 2) = 0, = 2, () :0 x = (2 - 1)(2 - 2) 0 x = 1 0 0 x = 0, .x + 1 2x + 1 5x + 1 :+ =2 3 61 : ... (x + 1 2x + 1 5x + 1 6. + 6. = 6. 3.(x + 1) + 2.().2 : 2x + 1) = 5x + 12 3 6 ( ).3 : X ( ).4 : 3x + 3 + 4x + 2 = 5x + 1 3x + 4x - 5x = 1 - 3 - 2.5 : 2x = -4 ( 2x -4= x = -222). 1 25 ( 1 ) 2 : (x - 1) = x(2 - 1) - 3 + 22 2 2 2 22 21 : , .x = B, (x - 1) = x(2 - 1) - 3 + 2 x - = 2x - x - 3 + 2 x - 2x + x = - 3, + 2(- 2 + 1)x = .- 3 + = =222 : , B 2 ( - 1) x = ( - 1)( - 2) () ( - 1) 0, , 1, (: x = .A) 23 : ( - 1)( - 2) - 2 . : x = x = - 1 ( - 1,) 2 , ( - 1) = 0, = 1, () : 0 x = 0, ..2 2x + 1 2 -x :- =x x + x (x + 1)22x + 1 2 -x-1 : .2 : ... .=x3(x + 1) x (x : + 1) .. . = x(x+ 1)= = = = = =2 22 2 2 22, ... 0.4 : : x(x + 1) 0 x 0 (x + 1) 0, x 0 x -1.x + 1 2 -x x(x + 1) - x(x + 1) = x(x + 1) (x + 1) -x(x + 1) x (x + 1) . 2 22 2 2 2 2 2 ' 2(x + 1) = -x- (x + 1) = -x (x + 1) = x x + 2x + 1 = x 2x + 1 = 0 2x = -11 x = - ( ( ), ).2 . x= = 0 x=0 > 0 x= > 0 x= < 0 < 0 x=-| | 26 ( 1 ) ( )2 1 :x + 3 x + 1 15 - x- = 2x - x - 3x + 2 = 02 4 3 x(x - 3)(2 - x) = 0 : = 0 A.B. = 0 = 0 = 02 22 2 2 :x + 1 x 2+ = (x + 1) + (5 - x) = 0x x + x (x + 1)

2 2 ... . ... . ( - , ). . + = 0 = 0 = 0.2 3 : (x - 1) - 2 = 3 + x .x = B (I) ( ).B 0, () , : x = .A = 0, , ... : 0.x = , 0, () . 0.x = 0, () . 4 : (x - ) = 3(x - 2). , x . .x = B : = 0 0. = 0 = 0.2 5 , (2 - 4)x = 0, ( - 3)x = + 3 . .x = B : = 0 0. = 0 = 0. 6 - 40%, - 300 ml - 58%. ;O ' , - , . 7 , 2 ( -). ( - ) 4 . , , . , ; , - x , :x x+ = 1 27

2 :x + 3 x + 1 15 - x- = 2x -2 4 3 x(x - 3)(2 - x) = 0 x - 3x + 2 = 0=12 Ex + 3 x + 1 15 - x x + 3 x + 1 15 - x- = 2x - 12. - 12. = 12.2x - 12.2 4 3 2 4 36(x + 3) - 3(x + 1) = 24x - 4(15 - x) 6x + 18 - 3x - 3 = 24x - 60 + 4x x = 3x = 0x = 3x = 2x = 2x = 12 2-756x - 3x - 24x - 4x = -60 - 18 + 3 -25x = -75 x =-25x = 0 x(x - 3)(2 - x) = 0 x - 3 = 02 - x = 0 x - 3x + 2 = 0 x - 2x - x + 2 = 0 x(x - 2) - (x - 2) = 0 (x - 2)(x - 1) = 0x - 2 = 0 x - 1 = 0 2 22 2 :x + 1 x 2+ =x x + x (x + 1) (x + 1) + (5 - x) = 02 2 2 Ex + 1 x 2 x + 1 x 2+ = + =(1)x x(x + 1) x x + x (x + 1) (x + 1) (1), = = = 1x = - 222 2 2 2 2 222 2. x 0x(x + 1) 0 , o (1) :x -1x + 1 x 2 x(x + 1) + x(x + 1) = x(x + 1) (x + 1) + x = 2(x + 1)x(x + 1) x (x + 1)(x + 1) - x = 0 (x + 1 + x)(x + 1 - x) = 0 (2x + 1) 1 = 0 2x + 1 = 0(, x = 1x = 52 2 )x + 1 = 0 (x + 1) + (5 - x) = 0 5 - x = 0 28 = = =2 : (x - 1) - 2 = 3 + x12 =-12 2 2 2 2 =-22 (x - 1) - 2 = 3 + x x - - 2 = 3 + x x - x = + 3 + 2( - 1)x = ( + 1)( + 2) ( - 1)( + 1)x = ( + 1)( + 2)() ( - 1)( + 1) 0, 1 -1, () ( : x = + 1) ( + 2)( - 1) ( + 1) + 2= - 1 ( - 1)( + 1) = 0, = 1 = -1, = 1 () :0.x = (1 + 1)(1 + 2) 0.x = 6, = -1 () :0.x = (-1 + 1)(-1 + 2) 0.x = 0, ( ). : (x - ) = 3(x - 2). , x .(x - ) = 3(x - 2) x - = 3x - 6 x - 3x = - 6 ( - 3)x = - 6(1) () e = 3 = 2 x , : - 3 = 0 = 3 - 6 = 0 3 = 6 2 , (2 - 4)x = 0, ( - 3)x = + 3 (2 - 4)x = 0 " = 2 (- 3. " :2 - 4 = 0 2 = 4 " = e2)x = + 3 " = 32 : - 3 = 0 - 3 = 0 + 3 0, , - 40%, 300 ml - 58%. ;40 x ml x ml. -10058 x + 300 ml (x + 300) ml.100, x = 700 , :40 58x + 300 = (x + 300) 40x + 30000 = 58x + 17400 18x = 12600100 100, 700 ml. 29 , - 2 ( ). ( ) - 4 . , , . , ; x , .1 2 , x 2x .2 x = 4 14 , 4x x . 4x x 2x x x- = 1 - = 1 = 12 4 4 4 4, 4 .27 7 66 2x - 4 = 3 2x = 7(2x - 4) = 3| 2x - 4 |= 32x - 4 = -3 2x = 1x = 0 x = 64x x - 64x = 0 x(x - 64) = 0x2 7 :(2x - 4) = 3 x =7x =21x =264x 66 6 6- 64 = 0x = 0 x = 0 x = 0 x = 64x = 64x = 2x = 0x = 2 30 2 2 :5x - 1 x + 4 1 - 4x+ = 2x - x (x + 1)(5 - x) = 0 x - x - 12 = 02 5 3

2 22 :x 1 4x+ = (x - 2x + 1) + (-6 + 5x - x ) = 0x + 3 x - 3 x - 92 2 2 : x - 2 = + 4x (x - 1) = x - (x - 1) = 3(x - ) + 2(1 - x)22 (x - 1) = x(2 - ) - 1 , x - 1 = (x + 1) .N x-2 x+2+ =1 -2 +2 2 (x+3) = + x+22 42x +1= x- () , (x -1) + = x+3 x. x-1 x-2 x- 4 x-5- = -x-2 x-3 x-5 x-6 4-7=-+3 (-2)x=2+1 . , , 40%, 300 ml 28%. ; , . 8 , 4 , 16 . , ; 2 , 3 - . 3 5 -. ; (. 8 , 19 ) 31 2 . 4 6. . (.46) , , 80 km/h 60 km/h . 100km;(.1 ) 40km/h. - 50km/h , 1 . ;(.200 km) 12 - ;(.1 5 . 27 .) 18 . .(.6) . - . 2/3 3/4 . 34 :. ,(. 18, 16). .(.10) 32| x - 1 | | 1 - x | :+ =| -2x + 2 | -73 21 : , ( - | x - 1 | | x - 1 |+ = 2. | x - 1 | -73 2| x - 1 | | x - 1 | 6 + 6 = 6 2 | x - 1 | - ).2 : 1 6 7 2 | x - 1 | +3 | x - 1 |= 12 | x - 1 | - 423 22 | x - 1 | +3 | x - 1 | -12 | x - 1 | = - 42.-7 3 : , : . | f(x) |= > 0, f(x) = . | f(x) |= < 0, , | x - 1 | = - 42 | x - 1 | = 6 -

x - 1 = 6 x = 6 + 1 x = 7 x - 1 = -6 x = -6 + .1 x = -5 :| x - 1 |+ | 2x - 4 |= 11 : - , . |x-1| x=1 |2x-4| x=2 s x < 1, :4- x + 1 - 2x + 4 = 1 -x - 2x = 1 - 1 - 42 -3x : = - 4 x =(, x < 1).3 1 x < 2, :

.x - 1 - 2 s> x + 4 = 1 x - 2x = 1 + 1 - 4 -x = - 2 x = 2 (, 1 x < 2). x 2, :x - 1 + 2x - 4 = 1 x + 2x = 1 + 1 + 4 3x = 6 x = 2 ( ).x - 1 2 +|x-1| -x-1 x+1 x+1|2x-4| -2x-4 -2x-4 2x+4 33 ( ) ( ) 8 : | x - 4 |= 6 | x - 4 |= 0 | x - 4 |= -3 3 | x - 4 |=| 2x - 3 || x - 4 | | 4 - x | | 2x - 8 |+ =3 2 4 :x = | x |= , > 0 x = -x = | x |=| | x = -2 9 : | x - 1 |= 3x + 5 || x - 3 | +1 |= 2 || x | -x |= 4 - 3 | x | x - 3 | x | +2 = 0 :x = | x |= , > 0 x = -x = | x |=| | x = -2 2 | | = 10 :3 | x - 1 | + 2 | x - 2 | - | x - 3 |= 0B x ' - . , . 34 : | x - 4 |= 6 | x - 4 |= 0 | x - 4 |= -3 3 | x - 4 |=| 2x - 3 || x - 4 | | 4 - x | | 2x - 8 |+ =3 2 4x - 4 = 6 | x - 4 |= 0 x - 4 = 0 | x - 4 |= 6x - 4 = -6 | x - 4 |= -3 - 3 < 03x - 12 = 2x - 3 3| x - 4 |=| 2x - 3| | 3x - 12|=| 2x - 3| 3x - 12 = x = 10 x = 4x = -2||=|-|3x - 2x = 12 - 3 -2x + 3 3x + 2x = 12 + 3x = 9 5x = 15| x - 4 | | 4 - x | | 2x - 8| | x - 4 | | -(x - 4) | | 2(x - 4) |+ = + =3 2 4 3 2 4| x - 4 | | x - 4 | | x - 4 | | x - 4 | | x - 4 | | x - 4 |+ = 2 6. + 6. = 6.3 2 4 3 2 22 x = 9x = 3| x - 4 | +3| x - 4 |= 3| x - 4 |2| x - 4 |= 0 x - 4 = 0 x = 4 A 3x + 5 < 0 .x - 1 = 3x + 5 5 A 3x + 5 > 0, x > - , | x - 1 |= 3x + 53 x - 1 = -3x - 52 : | x - 1 |= 3x + 5 || x - 3 | +1 |= 2 || x | -x |= 4 - 3 | x | x - 3 | x | +2 = 0}|x-3|+1> 0-2x = 64x = -45 5 {x = -3( - 3 < - ) ( - 1 > - )3 3x - 3 = 1 || x - 3| +1 |= 2 | x - 3| +1 = 2 | x - 3|= 1 x - 3 = -1 : | x |x | x | - x 0, :|| x | > >x = -1x = 4x = 22 2|x|=x, x 0|x|=-x, x >> > | -2| x | +2 = 0| x | (| x | -1) - 2(| x | -1) = 0 (| x | -1)(| x | -2) = 0| x | -1 = 0 | x |= 1| x | -2 = 0 | x |= 2 x = 1x = 2 35 x = 1, x = 2 x = 3. : (- , 1), [1, 2), [2, 3) [3, + ). : (- , 1) | x - 1 |= -x + 1 | x - :, : 3 | x - 1 | + 2 | x - 2 | - | x - 3 |= 0, :3(-x + 1) + 2(-x + 2) - (-x + 3) = 0 -3x + 3 - 2x + 4 + x - 3 = 0- 4x + 4 = 0 x = 1 ( 1 (- , 1)). : [1, 2) 2|= -x + 2 | x - 3|= -x + 3| x - 1 |= x - 1 | x - 2|= -x + 2 | x - 3|= -x + 3 :,, e | x - :1 |=3(x -x - 11) + 2(-x + 2) - (-x + 3) = 0 3x - 3 - 2x + 4 + x - 3 = 0 2x - 2 = 0( 1 [1, 2)). : [2, 3) :,, :3(x - 1) + 2(x - 2) - (-x + 3| x - 2|= x -) = 0 3x - 3 + 2x - 4 + x - 3 =2 | x0 6x - 10 =- 3|= -x + 3 e x = 1 50 x =35 ( [2, 3)).3 : [3, + ) :,, :3(x - 1) + 2(x - 2) - (x - 3) = 0 3x - 3 + 2x - 4 - x + 3 = 0 4x - 4 = 0 x = 1| x - 1 |= x - 1 | x - 2|=(x -2 | 1 [3, + )). x - 3 x|= 3 -e e , .x = 1 362 2 :| x - 2| | 4 - 2x | | x - 1 |= 5 | x + 7 |= 0 - 2| x + 3| +3| x - 6|= 0 + 1 =2 33| 2x - 6| +1 4 | 2x - 6| -3 | 2x - 6| +1 2| x - 1 | -1 | x - 1 | +1- =- = 32 2 3 3 22 : | x + 3|= -x + 2 | 2x - 1 |= -x + 3 || 2x - 4 | +2|= 6 || 2x | -x |= 6- | x | (3 - x) + | x - 3| -20 = 0 : | x + 2| - | x - 2|= 5 | x + 1 | - 3| x - 2| + | x - 3|= 0 | 2x - 1 | - 3| x + 2| + 2| x - 4 |= 3 - 5x 37 2 , :x+x+=0 ,, 0. , : =2-4. : > 0 =- 2. =0 =-2. 0 : x + = x + = x =2 2 2 2 4 = 0 : x +2| | | | ||\ . \ .| | | | | | |||\ . \ . \ .| | |\ .| |

\2 = 0 x + = x = -2 2 < 0 : (1) , . |. : x2+x+=0 0, 0 x1,x2. To x1,x2 : x2+x+=0 : S=x1+x2=-(1) To x1,x2 : x2+x+=0 : =x1.x2=(2) i Vietta. : x2+x+=0 : 2(1)2 2(2)x x x + x + = 0 + + = 0 x - (- )x + =